Potential targeting of B7-H4 for the treatment of cancer - Podojil, Joseph R. (Immunol Rev, 2017)
Observations noting the presence of white blood cell infiltrates within tumors date back more than a century, however the cellular and molecular mechanisms regulating tumor immunity continue to be elucidated. The recent successful use of monoclonal antibodies to block immune regulatory pathways to enhance tumor-specific immune responses for the treatment of cancer has encouraged the identification of additional immune regulatory receptor/ligand pathways. Over the past several years, a growing body of data has identified B7-H4 (VTCN1/B7x/B7S1) as a potential therapeutic target for the treatment of cancer. The potential clinical significance of B7-H4 is supported by the high levels of B7-H4 expression found in numerous tumor tissues and correlation of the level of expression on tumor cells with adverse clinical and pathologic features, including tumor aggressiveness. The biological activity of B7-H4 has been associated with decreased inflammatory CD4(+) T-cell responses and a correlation between B7-H4-expressing tumor-associated macrophages and FoxP3(+) regulatory T cells (Tregs) within the tumor microenvironment. Since B7-H4 is expressed on tumor cells and tumor-associated macrophages in various cancer types, therapeutic blockade of B7-H4 could favorably alter the tumor microenvironment allowing for antigen-specific clearance tumor cells. The present review highlights the therapeutic potential of targeting B7-H4.